Práticas integrativas e complementares em saúde : inserção no ensino, pesquisa e extensão no Centro de Ciências da Saúde de uma universidade pública - Amite, Cristiara Ferreira Lima (2024)
Introduction: The main public policy related to the topic, National Policy on Integrative and Complementary Practices in Health, reinforces the need for training human resources and continuing education for professionals. One of the main actions defined in the guidelines is the introduction of disciplines in professional health training, that is, at undergraduate and postgraduate levels. Objective: this work is to carry out a situational diagnosis of teaching, research and extension of PICS in the Health Sciences Center of a public university. This is a cross-sectional, documentary, descriptive study with a quantitative approach on the offering of subjects and content in PICS at the teaching, research and extension level from January 2020 to December 2023, with data collection carried out from June to December 2023. The study was developed within the scope of the Research in Integrative and Complementary Practices in Health (iPICS) research group. Results: In teaching, homeopathy and phytotherapy were optional subjects in undergraduate medicine, pharmacy and nutrition courses; in nursing, there was a mandatory subject that addresses the subject of PICS; in the multi-professional residency postgraduate course there is a PICS discipline on the transversal axis, which is mandatory; In the master's and doctorate programs in public health, master's degree in nursing and pharmaceutical sciences, there is also a record of related subjects and content. In research, there are two research groups, and the record of 174 scientific publications; in extension, 19 activities. Topics generally stand out in PICS, and specifically related to medicinal plants/phytotherapy in teaching (60%) and research (20.1%); and meditation (26.3%) in extension. Conclusions: the situational diagnosis highlighted the presence of PICS in undergraduate and postgraduate education, the existence of research groups and developed research and extension activities in the university's CCS